Handbook of family diversity - Demo, David (New York: Oxford University Press, Inc, 2000)
Contents : Am overview of family diversity: controversies,questions and values,reflections on family diversity:past and present,gender dynamics in families,family structure and family diversity,racial,ethnic and cultural diversities,class diversities in families,applicatios for working with families.
Incluye bibliografía
Keywords: Family Marriage